The Restructuring Process of the Singapore Tourism Board - Wee, Kevin Thian Hock (2007)
Corporate Restructuring efforts, especially those involving fundamental change to an organisation are complex processes. Due to the high incidence of unsuccessful restructuring efforts in the 1980s and 1990s, many frameworks of best practices have been developed by academics and practitioners to help management increase their chances of achieving a successful change process. Key practices include maintaining open communication channels between management, HR and staff; involving employees in the change process at early stages of the restructuring effort; ensuring that the restructuring effort is a long-term strategic plan rather than a "quick-fix" to cut costs and treating survivors and "laid-off" staff with sensitivity and dignity.